Acute diarrhoea among under five years old children of underprivileged community in Kota Kinabalu, Sabah - Mohd Faizal Madrim; Syed Sharizman Syed Abdul Rahim; Hasanain Faisal Ghazi; Than Myint; Khamisah Awang Lukman; Kamruddin Ahmed; Mohd Rohaizat Hassan; Alabed Ali A. Alabed; Mohammad Saffree Jeffree (Education in Action Club, 2021)
The severity of childhood diarrhoea is linked with poor socioeconomic status, unhygienic living environment, and caregiver’s behaviour. This study is to determine the risk factors and economic burden associated with diarrhoea in children under 5 years of age. A case-control study using convenience sampling method with 105 cases and 105 controls was performed in Menggatal health clinic, Kota Kinabalu, Sabah between March-June 2017. Younger caregivers, without formal education, poor knowledge, practice handwashing with water only and stopped breastfeeding were associated with diarrhoea. Household with poor economic status, a family of five and more, crowded, with a pet, unsafe drinking water, no sanitary toilet, unsanitary garbage disposal and consuming streetvendor food also associated with diarrhoea. The mean of total direct costs, total indirect costs and total incurred costs were (Ringgit Malaysia) RM 9.70, RM 59.40, and RM 14.30, respectively. As a conclusion, the risk factors for diarrhoea under 5 years of age still presents in Sabah. Environmental factors and hygienic practice are needed to control under 5 diarrhoea.